MINAT SISWA SMP N RSBI DAN SSN DI KOTA SEMARANG DALAM MEMILIH SMK - Santoso, Jarot Tri Bowo (Fakultas Ekonomi, Universitas Negeri Semarang, 2012)
The objective of this study is to know junior high school students interest in choosing vocational school (SMK). The research took place in 2 RSBI junior high schools and 2 SSN junior high schools in Semarang. The population of this study 854 students and the samples were 120 students.The data were collected by questionnaire and interview. Then, the data were analyzed by percentage description. The results showed that (1) RSBI junior high school students interest in choosing vocational school is very low. (2) SSN junior high school students interest in choosing vocational school is very low.